Mapping the intersection of sudden cardiac death and COVID-19: a comprehensive bibliometric analysis (2020–2024) - Bhattacharya, Sudip; Singh, Alok; Singh, Akanksha; Singh, Sukhpreet (Frontiers in Cardiovascular Medicine, 2024)
IntroductionA direct causal link between Sudden Cardiac Death (SCD) and COVID-19 is unproven, although current data suggest a plausible association.AimThis study aims to map and analyze the intersection of research on sudden cardiac death and COVID-19 through a comprehensive bibliometric analysis.MethodologyThis study searched the literature by applying the keywords “COVID-19” AND “Sudden Cardiac Death (SCD)”. Literature retrieved using the above keywords and published were included with a time limit from 1st January 2020 to 8th Aug 2024.ResultsThe bibliometric analysis of COVID-19 and Sudden Cardiac Death highlights key research trends from 2020 to 2024, revealing a rapid surge in scientific output during the pandemic. 2,915 articles were retrieved, with 70.5% being original research, reflecting a strong focus on new empirical evidence. The peak in publications occurred in 2021, driven by the urgent need to understand the cardiovascular implications of COVID-19. However, a decline in publications and citations in subsequent years suggests a shift in research priorities and a potential saturation in initial research areas. Leading institutions like Harvard Medical School, Mayo Clinic, and the University of Pennsylvania played a significant role, with the U.S., China, and the U.K. being top contributors. Despite fewer publications, China's research had a notable impact, indicated by high average citations per article. Keyword analysis identified “COVID-19” and “SARS-CoV-2” as dominant themes, with related terms like myocarditis and heart failure reflecting major cardiovascular concerns. Co-citation analysis revealed seminal works that shaped the discourse, with influential articles by Xu Z et al. and Guo T et al. frequently cited. The collaborative nature of research, especially among top institutions and countries like the U.S., Italy, and the U.K., was evident in network analyses. This study provides a comprehensive overview of the research landscape, highlighting significant contributions, emerging themes, and future research directions in understanding and mitigating the cardiovascular impacts of COVID-19.